Clinical and risk factor analysis of cloacal defects in the National Birth Defects Prevention Study. Issue 11 (28th September 2017) - Keppler‐Noreuil, Kim M.; Conway, Kristin M.; Shen, Dereck; Rhoads, Anthony J.; Carey, John C.; Romitti, Paul A.; ,
Abstract : Cloacal exstrophy (CE) and persistent cloaca (PC) (alternatively termed urorectal septum malformation sequence [URSMS]), represent two major cloacal defects (CDs). Clinical characteristics and risk factors often are studied for both defects combined, rather than exploring if these defects have different etiologies. We enumerated clinical features for 47 CE and 54 PC (inclusive of URSMS) cases from the National Birth Defects Prevention Study. Thirty‐three CE cases were classified as isolated and 14 as multiple (presence of unassociated major defects); respective totals for PC cases were 26 and 28. We compared selected child and maternal characteristics between 11, 829 non‐malformed controls and CE and PC cases using chi‐square or Fisher's exact tests. Compared to controls, CE and PC cases were statistically more likely ( p  < 0.05) to be preterm; CE cases were more likely to be multiple births. We conducted logistic regression analysis to estimate odds ratios and 95% confidence intervals for any CD, CE, and PC with selected self‐reported maternal prepregnancy and periconceptional (one month prior to 3 months following conception) exposures. In crude and adjusted analyses, we observed significant positive associations for any CD, CE, and PC with use of any fertility medication or assisted reproductive technology procedure. Significant positive associations observed only in crude analyses were any CD with maternal obesity or use of progesterone, any CD and CE with any x‐ray, and any CD and PC with use of folate antagonist medications. Our findings provide some of the first insights into potential differing etiologies for CE and PC.